Thai Private Hospitals' Innovative Healthcare Cultivation: An Exploratory Factor Analysis (EFA) - Punpukdee, Attakrai; Wattana, Chitinout; Punpairoj, Wachira; Srichuachom, Udomlak; Yaklai, Pimsara; Trongtortam, Suparawadee (MBA-KKU Journal, 2023)
Innovation in hospital healthcare is fundamental to differentiating treatment and creating consumer value. However, the creation and cultivation of innovative treatment in private hospitals has been overlooked. This study developed an innovative incubation evaluation tool based on an analysis of several incubation parameters. Based on a book study, interviews, and a poll of 280 health professionals at private Thai hospitals, this report was compiled. Corporate education, innovation, and empowerment are marketing-oriented ideas of value and usage context. In order to determine the efficacy of this Thai private hospital's efforts to incubate health care innovations, it is necessary to conduct an evaluation. It can be used to establish benchmarks for business innovation cultivation. It measures how innovatively a company is operating. However, this incubation method needs additional testing to continue evolving to become more effective.